Molecular and immunological characterization of Tri a 36, a low molecular weight glutenin, as a novel major wheat food allergen - Baar, A.; Pahr, S.; Constantin, C.; Scheiblhofer, S.; Thalhamer, J.; Giavi, S.; Papadopoulos, N. G.; Ebner, C.; Mari, A.; Vrtala, S.; Valenta, R. (J Immunol, 2012)
Wheat is an essential element in our nutrition but one of the most important food allergen sources. Wheat allergic patients often suffer from severe gastrointestinal and systemic allergic reactions after wheat ingestion. In this study, we report the molecular and immunological characterization of a new major wheat food allergen, Tri a 36. The cDNA coding for a C-terminal fragment of Tri a 36 was isolated by screening a wheat seed cDNA expression library with serum IgE from wheat food-allergic patients. Tri a 36 is a 369-aa protein with a hydrophobic 25-aa N-terminal leader peptide. According to sequence comparison it belongs to the low m.w. glutenin subunits, which can be found in a variety of cereals. The mature allergen contains an N-terminal domain, a repetitive domain that is rich in glutamine and proline residues, and three C-terminal domains with eight cysteine residues contributing to intra- and intermolecular disulfide bonds. Recombinant Tri a 36 was expressed in Escherichia coli and purified as soluble protein. It reacted with IgE Abs of ∼80% of wheat food-allergic patients, showed IgE cross-reactivity with related allergens in rye, barley, oat, spelt, and rice, and induced specific and dose-dependent basophil activation. Even after extensive in vitro gastric and duodenal digestion, Tri a 36 released distinct IgE-reactive fragments and was highly resistant against boiling. Thus, recombinant Tri a 36 is a major wheat food allergen that can be used for the molecular diagnosis of, and for the development of specific immunotherapy strategies against, wheat food allergy.
Keywords: Adolescent Allergens Amino Acid Sequence Animals Antigens; Amino Acid Wheat Hypersensitivity; Plant Cereals Child Child; Preschool Cross Reactions Female Glutens Humans Immunoglobulin E Male Molecular Sequence Data Molecular Weight Rats Sequence Homology